Pemaknaan Pengelolaan Radio Komunitas Secara Profesional dan Partisipasi (Studi Kasus Radio Silaturahim AM 720) - Ade Fadli Fachrul (STID DI AL-HIKMAH, 2017)
The study aims to find answers about the definition of a professional to manage community radio and how to build a participatory community radio with the corresponding reference. This research uses qualitative descriptive konstruktivistis paradigm that will depict the real conditions and the existence of Radio friendship. The conclusion that in the management of community radio professional aspect is absolutely necessary as the demand to continue broadcasting in order to expand the number of listeners as well as for the management of radio quality. By upholding the professional level will provide improved quality and audience loyalty will be maintained and sustained. Community radio can survive by increasing the amount of audience participation, because community radio was born and grew from the desire of the community this sendiri.Partisipasi not merely as a listener but an active contribution in the form of donors, thinking, evaluation and monitoring of the sustainability of the radio broadcasts.